On the influence of environment on star-forming galaxies. Issue 3 (6th August 2018) - Xie, Lizhi; De Lucia, Gabriella; Wilman, David J; Fossati, Matteo; Erwin, Peter; Gutiérrez, Leonel; Kulkarni, Sandesh K
ABSTRACT: We use our state-of-the-art semi-analytic model for GAlaxy Evolution and Assembly (GAEA), and observational measurements of nearby galaxies to study the influence of the environment on the gas content and gaseous/stellar disc sizes of star-forming galaxies. We analyse the origin of differences between physical properties of satellites and those of their central counterparts, identified by matching the V max of their host haloes at the accretion time of the satellites. Our model nicely reproduces the differences between centrals and satellites measured for the H i mass, size of the star-forming region, and stellar radii. In contrast, our model predicts larger differences with respect to data for the molecular gas mass and star formation rate. By analysing the progenitors of central and satellite model galaxies, we find that differences in the gas content arise after accretion, and can be entirely ascribed to the instantaneous stripping of the hot gas reservoir. The suppression of cold gas replenishment via cooling and star formation leads to a reduction of the cold gas and of its density. Therefore, more molecular gas is lost than lower density H i gas, and model satellites have less molecular gas and lower star formation rates than observed satellites. We argue that these disagreements could be largely resolved with the inclusion of a proper treatment for ram-pressure stripping of cold gas and a more gradual stripping of the hot gas reservoir. A more sophisticated treatment of angular momentum exchanges, accounting for the multi-phase nature of the gaseous disc, is also required.